4 - Regulatory Bodies, Academic Freedom and Institutional Autonomy in Africa: Issues and Challenges – The Nigerian Example - Elijah Adewale Taiwo (Journal of Higher Education in Africa, 2011)
Academic freedom is often described as a four-fold right of a university to determine for itself on academic grounds, who may teach, what may be taught, how it shall be taught, and who may be admitted to study. It also entails the freedom of a university to select its own staff and to determine its own standards, as well as the freedom of both staff and students to free expression in their teaching, studying, publishing and research. Institutional autonomy, on the other hand, is the freedom an educational institution en- joys in managing its internal affairs without undue interference from outside bodies or persons, especially from the government or its agencies. An effec- tive enjoyment of academic freedom, however, requires institutional autonomy. In recent times, Nigerian universities have witnessed many issues challeng- ing their academic freedom and institutional autonomy such as summary dismissal of university teachers for being critical of government educational policies and other related issues. Against this background, this article ar- gues that the establishment of regulatory bodies such as the Nigerian Uni- versities Commission, the Joint Admission and Matriculation Board and the like has eroded the previous autonomy and freedom enjoyed by the univer- sities in the four cardinal ways mentioned above. The article advocates a system which adequately guarantees academic freedom. It also commends to Nigeria and other African countries the South African position which guarantees the right to academic freedom and scientific research in its Con- stitution.